Efficacy of continuous positive airway pressure (CPAP) in the prevention of cardiovascular events in patients with obstructive sleep apnea: Systematic review and meta-analysis. (August 2020) - Labarca, Gonzalo; Dreyse, Jorge; Drake, Lauren; Jorquera, Jorge; Barbe, Ferran
Summary: Obstructive sleep apnea (OSA) commonly occurs in patients with increased cardiovascular (CV) risk, and continuous positive airway pressure (CPAP) is the preferred therapy for these patients. The aim of this review was to evaluate the efficacy of CPAP for CV prevention in OSA patients. We conducted a systematic review of randomized controlled trials (RCTs). Two independent reviewers explored different databases and evaluated the risk of bias. Outcomes were defined as the relative risk (RR) of major CV events (MACEs), CV mortality, myocardial infarction, unstable angina, stroke, atrial fibrillation (Afrib) and heart failure. We performed both subgroup and meta-regression analyses by sleepiness status, adherence, and OSA severity. The certainty of evidence was rated according to GRADE. A total of 8 RCTs and 5817 participants were included. The results showed an RR of 0.87 (CI, 0.70–1.10) for MACEs, an RR of 0.94 (CI, 0.62–1.43) for CV mortality, an RR of 1.04 (CI, 0.79–1.37) for myocardial infarction, an RR of 1.05 (CI, 0.51–2.15) for unstable angina, an RR of 0.92 (CI, 0.68–1.23) for heart failure, an RR of 0.94 (CI, 0.71–1.26) for stroke, and an RR of 0.94 (CI, 0.54–1.64) for Afrib. Subgroup analysis and meta-regression revealed no effect on our proposed outcomes. Although there is no evidence that CPAP therapy improves CV outcomes, concerns regarding risk of bias, CPAP adherence, and the population included in each RCT may have reduced the strength of the findings to support the benefit in all patients, and future research exploring these relevant outcomes is needed. Review register: PROSPERO CRD42019145803.